2019
DOI: 10.1111/bor.12380
|View full text |Cite
|
Sign up to set email alerts
|

Additive effects of climate change and human hunting explain population decline and extinction in cave bears

Abstract: Cave bears (Ursus spelaeus) are an iconic component of the European late Quaternary Ice Age megafauna. Recent demographic analyses based on cave bear mtDNA sequences and refined radiocarbon dating indicate that cave bear population size and genetic diversity started to decline some 50 kilo years ago (kya). Hence, neither the coldest phase of the last glaciation (started some 24 kya), nor the colonization of Europe by Palaeolithic hunters (started some 45 kya) coincides with the beginning of population decline.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 64 publications
(170 reference statements)
1
7
0
Order By: Relevance
“…Although hypothesizing on the specific vegetal resource that cave bears were specialized to feed on is tempting, our results indicate that cave bears were specialized to feed upon tough vegetal resources of the high-alpine biome, which supports the climate-driven hypothesis to explain their extinction at the beginning of the Last Glacial Maximum when the primary productivity that the cave bear fed upon was dramatically lowered [3][4][5].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Although hypothesizing on the specific vegetal resource that cave bears were specialized to feed on is tempting, our results indicate that cave bears were specialized to feed upon tough vegetal resources of the high-alpine biome, which supports the climate-driven hypothesis to explain their extinction at the beginning of the Last Glacial Maximum when the primary productivity that the cave bear fed upon was dramatically lowered [3][4][5].…”
Section: Discussionsupporting
confidence: 72%
“…Some authors propose that cave bears were adapted to feed exclusively on vegetal resources from 100 000 to 20 000 years ago [2], without evidence of a dietary shift towards omnivory at a time of lowered vegetation productivity during the Last Glacial Maximum [3]. Both the lack of dietary flexibility and possible human competition are proposed to be critical factors in explaining the extinction of cave bears [4,5]. Recently, Pérez-Ramos et al [6] demonstrated that large paranasal sinuses were likely selected in cave bears to overcome longer hibernation periods, but the sinuses also compromised the skulls biomechanically.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial DNA and population demographics suggest the cave bear Ursus spelaeus suffered a dramatic population decline starting at 50 ka (Mondanaro et al 2019). The same rapid decline in exactly the same time interval pertains to the Eurasian populations of cave lion Panthera leo spelaea (Stuart and Lister 2011), and cave hyena Crocuta crocuta spelaea (Stuart and Lister 2014).…”
Section: Discussionmentioning
confidence: 89%
“…In fact, the best radiometric estimates for the extinction date of Homo neanderthalensis (at 40 ka, Higham et al 2014) the giant rhino Elasmotherium sibiricum (Kosintsev et al 2019) the camel Camelus knoblochi , the giant deer Sinomegaceros yabei , the narrow‐nosed rhino Stephanorhinus hemitoechus , the antelope Spiroceros kiakhtensis and the Asian straight‐tusked elephant Palaeoloxodon naumanni are all concentrated in the narrow 45–37 ka interval (Stuart and Lister 2012). Mitochondrial DNA and population demographics suggest the cave bear Ursus spelaeus suffered a dramatic population decline starting at 50 ka (Mondanaro et al 2019). The same rapid decline in exactly the same time interval pertains to the Eurasian populations of cave lion Panthera leo spelaea (Stuart and Lister 2011), and cave hyena Crocuta crocuta spelaea (Stuart and Lister 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation